KRISIS SISTEM LEGISLASI INDONESIA MENURUT ETIKA DISKURSUS JURGEN HABERMAS - Indra Lukman Siregar; Mexsasai Indra; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The factual symptoms show that the fluctuating state of public trust and the sub-systemsof social life do not work in balance and harmony with what the public wants because the worldof people's lives is shrinking in the face of power and the power of the money system. Whenthe active participation of the people is removed from the decision-making arena and directlytaken over by the control of power, the people, who are in fact the holders of sovereignty, areonly justified in claiming decisions in the name of democracy. This phenomenon is clearly seenin the legislative process in Indonesia.We can never forget that, in the last 5 (five) years alone, there have been many